Learning English in Pre-school age - Parents' Beliefs - Teplá, Lucie (Univerzita Pardubice, 2013)
The main topic of the bachelor thesis is parents' beliefs about early English language learning. The theoretical part starts with a look into the origin and development of the pre-school institutions in the Czech Republic. Then the focus is on a Framework Education Programme for Pre-primary Education and its conception and contribution to the English pre-school classes. An emphasis is placed on overall description of psychological development of the pre-school age child and also mainly on the first and the second language acquisition. At the end of this paper benefits and possible risks of early language learning are described as well as introduction into the belief system. The practical part is dedicated to the research that was conducted in order to discover parents' reasons for early language learning.
Názory rodičů na výuku anglického jazyka u dětí v předškolním věku
Keywords: předškolní žáci; rámcový vzdělávací program; osvojování si druhého jazyka; názory rodičů; pre-school learners; framework education programme; second language acquisition; parents' beliefs